STUDY OF MICROCIRCULATION OF THE EYEBALL IN THE SURGICAL TREATMENT OF INTRAOCULAR HEMORRHAGE - A. V. Malyshev; V. N. Trubiun; S. M. Makkaeva; S. V. Janchenko; Z. ZH. Alrashid; Y. A. Gusev; L. Sh. Ramazanova (Кубанский научный медицинский вестник)
This article describes changes in the microcirculation of the eyeball in patients with hemophthalmus during vitrectomy. We examined 24 patients who underwent vitrectomy, according to testimory local lasercoagulation of retinal vessels. In the early postoperative period marked a temporary deterioration in microcirculation caused by eye injury during surgery. Positive effect of surgery to remove a blood clot on the state microhemodynamics achieved in the late postoperative period, manifested in the increasing speed performance perfusion eye capillaries and eliminating the overwhelming influence of the passive component in the system of regulation of microcirculation. Hemophthalmia holding surgical removal leads to a significant improvement of the basic microcirculation eyeball in the late postoperative period.